Opportunities For Development Of Agricultural Services In Uzbekistan (Open Herald: Periodical of Methodical Research, 2024)
This article examines the development of agricultural services, which, based on the available economic opportunities, are an important type of service provision in the republic. Also, this article substantiates important features, as well as the main directions for improving the organizational and economic mechanisms of its development.